Environmental noise exposure, early biological risk and mental health in nine to ten year old children: a cross-sectional field study - Stansfeld Stephen A; Clark Charlotte; Crombie Rosanna (BMC, 2011)
Abstract Background Previous research suggests that children born prematurely or with a low birth weight are more vulnerable to the mental health effects of ambient neighbourhood noise; predominantly road and rail noise, at home. This study used data from the Road Traffic and Aircraft Noise Exposure and Children's Cognition and Health (RANCH) study to see if this finding extends to aircraft and road traffic noise at school. Methods Children and their parents from schools around three European airports were selected to represent a range of aircraft and road traffic noise exposure levels. Birth weight and gestation period were merged to create a dichotomous variable assessing 'early biological risk'. Mental health was assessed using the Strengths and Difficulties Questionnaire (SDQ). Complete data were available for 1900 primary school children. Results Children who were 'at risk' (i.e. low birth weight or premature birth) were rated as having more conduct problems and emotional symptoms and poorer overall mental health than children not at risk. However, there was no interaction between aircraft or road traffic noise exposure at school and early biological risk. Conclusions Data from the RANCH study suggests that children with early biological risk are not more vulnerable to the effects of aircraft or road traffic noise at school on mental health than children without this risk; however they are more likely to have mental ill-health.